Citra Sempurna? Pola Visual dan Makna Foto Pre-Wedding - , AGUS HERU SETIAWAN, Dr. G. R. Lono Lastoro Simatupang, M. A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis highlights the trend of the use of pre-wedding photography as part of a wedding celebration procession in Yogyakarta and the meaning contained in the images, both from the point of view of those who see it as well as from the perspective of the couple who came up with the idea of a photo itself. In addition, also saw changes in society arising from the trend of the use of the photo. This study uses visual data from personal collections of photographers and photo studios in Yogyakarta. Moreover, the writer conducted in-depth interviews with photographers, the bridal couples who used pre-wedding photos and the people who have been indirectly involved in the process of making the photos, such as wives of photographers, parents of the couples, etc. Pre-wedding photography is the result of the creative development of wedding photography, which in itself is a part of technological change that was brought from the usage of digital cameras as opposed to analogue cameras, brought a variety of social contexts, greater than what we, as viewers, actually see. Pre-wedding photography be imagined as a representation media that provides the perfection of self image and the freedom for bridal couples to express desires and dreams for themselves as a couple, freeing from the involvement of parents and families is a mythe who created by photo industry. A reflected formed and facilitated its development for the benefit of the photo industry.